Intermolecular recombination between DNAs introduced into mouse L cells is mediated by a nonconservative pathway that leads to crossover products. - Lin, F L (1990)
We describe experiments designed to measure the efficiency of intermolecular recombination between mutant herpesvirus thymidine kinase (tk) genes introduced into mouse L cells. Recombinants were scored as stable transformants containing a functional tk gene. The two recombination substrates used were ptkB8, a pBR322-based plasmid containing a mutant tk gene, with a BamHI linker in an SphI restriction site that is centrally located within the gene, and mp10tk delta 3' delta 5', an mp10 vector with a tk gene deleted at both the 3' and 5' ends. The only homology shared by the two DNAs is 885 base pairs within the tk gene. To determine whether the double-strand break repair model that has been used to explain recombination in yeast cells (J. W. Szostak, T. L. Orr-Weaver, R. J. Rothstein, and F. W. Stahl, Cell 33:25-35, 1983) can account for recombination during the introduction of these DNAs into mammalian cells, we transformed cells with BamHI-linearized ptkB8 and supercoiled mp10tk delta 3' delta 5' replicative-form DNA. These two DNAs should recombine efficiently according to that model and should generate gene conversion products. In this reaction, the supercoiled DNA acts as the donor of information to repair the cleaved tk gene. Our results indicated that the efficiency of this reaction was very low (less than 10 transformants were obtained per 0.1 microgram of each DNA used in the reaction per 10(6) cells). In contrast, if BamHI-cleaved ptkB8 DNA was cotransformed into cells along with a circular DNA molecule containing a tk gene deleted only at its 3' end or only at its 5' end (mp10tk delta 3' or mp10tk delta 5'), then the efficiency of recombination could be more than 4 orders of magnitude higher than it was with circular mp10tk delta 3' delta 5' DNA. Recombination frequencies were highest when the tk delta 3' or tk delta 5' DNA used was cleaved at the tk deletion junction. Southern analyses of DNA from TK+ transformants generated with BamHI-cleaved ptkB8 and BamHI-cleaved mp10tk delta 3' DNAs indicated that recombination was almost always associated with the reassortment of markers flanking the reconstructed tk DNA. Together, these results are more consistent with the nonconservative single-strand annealing model for recombination that we proposed several years ago (F.-L. Lin, K. Sperle, and N. Sternberg, Mol. Cell. Biol. 4:1020-1034, 1984) than they are with the double-strand break repair model.